Integrated STEM 3.0 Approach to Enhance Critical Thinking Skills: An Empirical Evidence - Sukamto, Ismu; Maulina, Hervin; Widyastuti, Widyastuti; Tias, Ika Wulandari Utamining; Huda, Tiyas Abror; Maulina, Dina (Jurnal Pendidikan Progresif, 2022)
Integrated STEM 3.0 Approach to Enhance Critical Thinking Skills. Critical Objectives: This study aimed to examine the effect of the STEM 3.0 approach assisted by real material and virtual simulation to enhance the CTS. Methods: The research method used Quasi-Experimental Designs with Matching-Only Pretest-Posttest Control Group Design. The subjects of this study were high school students of Class XI in Surabaya. Findings: Based on the research data, the increase in the CTS of students in the 2 experimental classes was classified as moderate with an average n-gain value of students in class A2 of 0.69 and class A5 of 0.63 while the increase in CTS in the control class was classified as moderate with a lower value (a score of 0.36). Based on the results of statistical tests, there is a significant difference between the experimental class and the control class. Conclusion: Thus, it is concluded that the integrated STEM 3.0 approach can enhance the CTS. Keywords: integrated STEM 3.0, CTS, real material, virtual simulations.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202219